Globalization and the de-Anglicization of English - Gillian Perrett (TEFLIN Journal: A publication on the teaching and learning of English, 2005)
Abstract: With the development of globalization cultural issues associated with TEFL are inevitably being transformed. In the modern world peoples were grouped within nations and communicated in speech communities largely within their own countries; communication outside the boundaries of the national speech community was not the norm for the majority of people. In the post-modern world the position of these vertical boundaries is changing to horizontal and an upper stratum of society (wherever it is located) is able, with computer technology, to communicate relatively freely across national boarders. The lingua franca of this communication is English. It is not the English of any particular country and it is developing new cultural norms, especially in the electronic media. In one stratum professional functions dominate and electronic usage closely reflects familiar print genres. In other strata more interpersonal functions occur and at the same time the language is moving away from old standard forms; this is most apparent in email and chat room discourse. Teachers have to shift from traditional notions of culture and situation and embrace the new electronic forms, finding ways to help their students participate fully in the new intercultural situation.